1972
DOI: 10.1530/jrf.0.0280015
|View full text |Cite
|
Sign up to set email alerts
|

Water Content, Specific Gravity and Concentrations of Electrolytes in Bull Spermatozoa

Abstract: The water content of epididymal bull spermatozoa in media of osmolalities corresponding to those of seminal plasma and to the fluids from the cauda epididymidis was determined by a gravimetricvolumetric method as 0\m=.\586\ m=+-\ 0\m=.\0052and 0\m=.\512\m=+-\0\m=.\0086ml per ml of cells, respectively. It was related to the ionic concentrations in mmol/ litre of spermatozoa determined by the conversion of the mean values of the major cations expressed as mequiv./litre, mg/100 g, or mg/100 ml, established by pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
2

Year Published

1972
1972
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 28 publications
1
13
2
Order By: Relevance
“…The osmolalities of these Ringer solutions are approximately 0-353 osmol, i.e. they are isosmotic with the fluids from the cauda epididymidis (see Drevius, 1972a). The solutions also contained 0-1 % of glucose.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The osmolalities of these Ringer solutions are approximately 0-353 osmol, i.e. they are isosmotic with the fluids from the cauda epididymidis (see Drevius, 1972a). The solutions also contained 0-1 % of glucose.…”
Section: Methodsmentioning
confidence: 99%
“…Bull spermatozoa were obtained from the cauda epididymidis of gonads from slaughtered bulls and collected in NaCl Ringer solution (see below) as in previous studies (Drevius, 1971a(Drevius, , 1972a.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation is far different for spermatozoa, since their volume cannot easily be measured in situ, the osmolality of the surrounding fluid varies with their location in both male and female tracts, and the ability to regulate volume is developed during epididymal transit (see below). Drevius (1972b) considered 353 mmol/kg (the osmolality of cauda epididymidal plasma) to be isotonic medium for bovine cauda epididymidal sperm, whereas Du et al (1994) and Noiles et al (1995) considered 286 -290 mmol/kg "isosmotic" for murine sperm, although far from the osmolality existing within either the epididymis (415 mmol/kg) (Yeung et al, 1999) or uterus (327 mmol/kg: . Drevius (1972a) found that mature bovine sperm were "perfect osmometers" (whose volume varies inversely with osmolality) by calculating the volume of caudal sperm from diameters of their coiled tails.…”
Section: Response Of Sperm Volume Tomentioning
confidence: 99%
“…This indicates that when human spermatozoa are frozen at about 10" C/min, there is sufficient dehydration at -30" C, so that cryoinjury due to intracellular ice crystal formation is avoided. The low water content and the higher surface to volume ratio of spermatozoa when compared with most mammalian cells (Salisbury and Van Demark -1961;Drevius -1972) may explain this result. The above findings are in contradiction to Mazur's two-factor theory and to the finding in the bull that rapidly frozen semen results in maximal survival when rapidly thawed Rodriquez et al -1975).…”
Section: Discussionmentioning
confidence: 99%